PROTOTIPE SISTEM OTOMATIS LAMPU ULTRAVIOLET-B PADA KANDANG BURUNG DENGAN SENSOR SUHU BERBASIS MIKROKONTROLER ARDUINO - Vina Septiana Windyasari; M. Andika Candra (Jurnal Algoritma, Logika dan Komputasi, 2020)
Today's technological developments are not only limited to entrepreneurs, students, communities, but also to farmers. Phenomena that often occur especially in poultry farmers include problems with the temperature in closed rooms that certainly change so as to affect the growth and survival of birds, and weather that is too cold or hot can affect comfort in birds, so as to help and enrich the development of technology-based microcontrolle, in this design using microcontrolroller Arduino Uno, in this study designed a prototype that is the design of automatic setting of Ultraviolet-B lamps with temperature sensor DHT11 that can be applied to closed aviary especially for chirping birds, and such as the use of heating lamps in closed aviary is using Ultraviolet-B lamps as a substitute for sunlight that is beneficial for living needs as well as the growth process of birdsong to get a fairly warm irradiation, helping bird farmers who can be adjusted or programmed to the required temperature , in this design using the model prototype system development method, the trial was carried out by controlling incoming light so that it affects the temperature of the drum that produces the detection of DHT11 temperature sensor automatically ultraviolet-B lamp can light with the provisions of temperature <29.50°C and lights off at a temperature of ≥32°C that can be displayed on the LCD layer, so it can help to control the temperature and lights automatically.Keywords: Microcontrolle, Arduino Uno, Ultraviolet-B Lamp, DHT11 Temperature Sensor